Normative data of potential young Malaysian athlete for talent identification decision support system - Soeed, Kamaruzaman (2016)
This study focused on the development of normative data of potential young Malaysian athlete for the Sports Talent Identification Decision Support System (STIDSS). The system helps to smoothen the process of the sports talent identification program in order to produce potential future athletes in Malaysia. Current approaches of talent identification programs only focused on physical and psychological attributes. The newly developed STIDSS focuses on four main attributes which include physical, physiological, psychological and sociological components. Basically, assessment of these attributes is the main focus of this study and acts as part of the objectives of the study, in line with the evaluation of the effectiveness of STIDSS. Four related anthropometric measurements and nine field tests were used to assess the ability of an individual’s physical fitness. The 20 m multistage shuttle run test was used to test maximum oxygen uptake (VO2max) for physiological while the mental toughness and the level of parental support tests were used to investigate psychological and sociological attributes. A total of 537 ball sports, racket sports and target sports junior athletes, aged 13 years old were selected from the Malaysian Sports School and State Sports School to be involved in the field testing. A total of 85 participants was involved in the testing of the usability of the system and 374 junior athletes were tested to evaluate the accuracy of the system based on physical and physiological characteristics. Three sets of questionnaires were used to test the level of mental toughness, the level of parental support and the usability of STIDSS. Findings showed that for ideal anthropometrics characteristics, only male racket sports and female ball sports achieved superior standard. This study developed a new norm based on the total population of junior potential national athletes which covered both Malaysian sports school and nine state sports schools. Speed, agility, reaction time and cardiovascular endurance did not contribute directly to the performance of target sports but it significantly contributed to ball sports and racket sports. This study found that measurement of VO2max uptake is not a priority element for target sports. Most junior athletes have moderate mental strength, however there were big differences between the target sports and the racket sports in term of reboundability, pressure, concentration, confidence and motivation. This study also found that very few parents strongly supported their children to be involved in high level competitions. Majority of respondents were satisfied with the usability of the developed STIDSS and the accuracy test was satisfactory. Thus, the use of STIDSS is proven to be appropriate in the process of selecting young talent to match specific sports. Future research may include wider variety of sports to improve the system.